2002
DOI: 10.1523/jneurosci.22-10-04015.2002
|View full text |Cite
|
Sign up to set email alerts
|

Caspase Cascades in Human Immunodeficiency Virus-Associated Neurodegeneration

Abstract: Many patients infected with human immunodeficiency virus-1 (HIV-1) develop a syndrome of neurologic deterioration known as HIV-associated dementia (HAD). Neurons are not productively infected by HIV-1; thus, the mechanism of HIV-induced neuronal injury remains incompletely understood. Several investigators have observed evidence of neuronal injury, including dendritic degeneration, and apoptosis in CNS tissue from patients with HAD. Caspase enzymes, proteases associated with the process of apoptosis, are synth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

22
233
0
1

Year Published

2002
2002
2010
2010

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 208 publications
(256 citation statements)
references
References 72 publications
(103 reference statements)
22
233
0
1
Order By: Relevance
“…The number of neurons was quantified by immunostaining for the neuron-specific markers microtubule-associated protein-2 (MAP-2) and NeuN, and apoptotic nuclei were identified morphologically after staining nuclei with the DNA dyes Hoechst 33342 or propidium iodide. 11,12 In two out of three experiments shown in Figure 1 and in seven out of twenty-seven experiments performed with the different WT and chemokine receptor-deficient murine cerebrocortical cultures, TUNEL (Apoptosis Detection System/Fluorescein, Promega, Madison, WI, USA) was applied to detect fragmented nuclear DNA in apoptotic nuclei. 11,31 Neuronal survival was calculated from the percentage of neurons remaining after subtraction of those that had undergone apoptosis.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The number of neurons was quantified by immunostaining for the neuron-specific markers microtubule-associated protein-2 (MAP-2) and NeuN, and apoptotic nuclei were identified morphologically after staining nuclei with the DNA dyes Hoechst 33342 or propidium iodide. 11,12 In two out of three experiments shown in Figure 1 and in seven out of twenty-seven experiments performed with the different WT and chemokine receptor-deficient murine cerebrocortical cultures, TUNEL (Apoptosis Detection System/Fluorescein, Promega, Madison, WI, USA) was applied to detect fragmented nuclear DNA in apoptotic nuclei. 11,31 Neuronal survival was calculated from the percentage of neurons remaining after subtraction of those that had undergone apoptosis.…”
Section: Methodsmentioning
confidence: 99%
“…Nuclear DNA was stained with H33342. Deconvolution microscopy was performed as described earlier 12 ; filters for AMCA, CY3, CY5 and FITC were used for four-color image capture and a 'nearest neighbor' algorithm for deconvolution (Slidebook software, Intelligent Imaging Innovations, Denver, CO, USA).…”
Section: Methodsmentioning
confidence: 99%
“…Gp120 also causes neuronal dysfunction and death in rodents in vivo. 40 Specific inhibitors of both the Fas/tumor necrosis factor-a/ death receptor pathway and the mitochondrial caspase pathway can reduce the gp120-induced neuronal apoptosis. 40 When added to mixed cultures of murine neurons and glial cells, gp120 only causes apoptosis when such cells are derived from p53-expressing mice.…”
Section: Cell Killing By Soluble Gp120mentioning
confidence: 99%
“…40 Specific inhibitors of both the Fas/tumor necrosis factor-a/ death receptor pathway and the mitochondrial caspase pathway can reduce the gp120-induced neuronal apoptosis. 40 When added to mixed cultures of murine neurons and glial cells, gp120 only causes apoptosis when such cells are derived from p53-expressing mice. Reconstitution experiments in which p53 þ / þ and p53 À/À neurons and glial cells were mixed demonstrated that both cell types (neuronal þ glial) were required for the lethal response to gp120 and that both of them had to express p53 so that neurons would die upon gp120 addition.…”
Section: Cell Killing By Soluble Gp120mentioning
confidence: 99%
“…In a disease of chronic inflammation, incremental stages of increasing stress do not immediately overwhelm a cell's capacity to respond, the stress required to overwhelm cellular repair and homeostatic mechanisms compromise synaptic function long before the induction of cell death mechanisms. In HAD, damage to dendritic arbors and reduction in synaptic density are important neuropathological signatures of HIVE (111,112). This type of damage to the neural network is thought to be an early event in the pathway leading to neuronal dropout via apoptosis (55,113).…”
Section: Excitotoxicitymentioning
confidence: 99%